SUBORDINATE CLAUSES IN ADULTERY NOVEL - Wahyu Nugraha; I Komang Sulatra; Purwati (SPHOTA: Jurnal Linguistik dan Sastra, 2020)
A subordinate clause (dependent clause) is a clause that cannot stand alone as a complete sentence because it does not express a complete thought. It explains and gives more information to the main clause. There are three major types of subordinate clause such as: Complement Clause, Relative Clause, and Adverbial Clause (Miller, 2002:63). This research is a library research that aims to find out types and functions of subordinate clause found in Adultery. This research uses several theories from expert in other to analyze the problems in this study. The book written by Jim Miller (2002) entitled An Introduction to English Syntax and the book written by Bas Aarts (2001) entitled English Syntax and Argumentation, Second Edition are used. It is stated that there are three major types of subordinate clause that can be recognized as Complement clause, Relative clause, and Adverbial Clause. Then, the clause functions such as Clauses Functioning as Subject, Clause Functioning as Direct Object, Clauses Functioning as Adjunct and Clauses Functioning as Complements within Phrases. The result of this research shows that three major types of subordinate clause are found. Furthermore, the clause functions are also found as well, however only Clauses Functioning as Subject weren’t found in this research.